2022
DOI: 10.53850/joltida.884992
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Dissection Table: A Supplemental Learning Aid for a Physical Therapy Anatomy Course

Abstract: While cadaver dissection and prosection are deemed quintessential methods for studying anatomy, these methods are attenuated by the flat, 2-D structures incorporated into didactic segments of the anatomy courses that minimize students' ability to comprehend anatomy, leading to constraints in the teaching and learning experience. Several tools, such as 3-D virtual anatomy apps and anatomical models, enhance teaching and students' understanding of gross human anatomy. The Anatomage, a virtual anatomy dissection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The importance of using a variety of learning approaches to support a diversity of student learning needs was reported in one experimental study, five observational or cross-sectional studies, and one scoping review. Four studies found that methods that effectively teach visual and spatial relationships using technological (e.g., 3D apps and computer-based visual media) and nontechnological (e.g., 2D anatomical model cutouts) were valued by and beneficial for a variety of anatomy learners ( Daly, 2010 ; Gangata, 2008 ; Rosario, 2021b ; Toth-Cohen, 1995 ). Two studies and one scoping review reported that multiple teaching methods facilitated learner engagement and understanding of anatomy ( Dempsey et al, 2021 ; Rosario, 2021a ; Thomas et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of using a variety of learning approaches to support a diversity of student learning needs was reported in one experimental study, five observational or cross-sectional studies, and one scoping review. Four studies found that methods that effectively teach visual and spatial relationships using technological (e.g., 3D apps and computer-based visual media) and nontechnological (e.g., 2D anatomical model cutouts) were valued by and beneficial for a variety of anatomy learners ( Daly, 2010 ; Gangata, 2008 ; Rosario, 2021b ; Toth-Cohen, 1995 ). Two studies and one scoping review reported that multiple teaching methods facilitated learner engagement and understanding of anatomy ( Dempsey et al, 2021 ; Rosario, 2021a ; Thomas et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study found that learners had improved outcomes on bellringer examination when trained to draw during cadaveric dissection ( Chaudhuri, 2021b ). Five studies examined the use of computer-assisted instruction in occupational therapy education and found positive effects on academic achievement (e.g., exams and grades) from methods ranging from “low-tech” (e.g., computer-based graphics and videos) to “high-tech” applications (e.g., AnatomyTV) ( Bowdish et al, 1998 ; Chan, 1999 ; Langfield et al, 2018 ; Mathiowetz et al, 2016 ; Rosario, 2021a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, scholars have proposed virtual dissections with arguments in favor of their benefits [7][8][9]. It remains noteworthy that dissection is procedural, methodical, scientific, and scholarly; as such, it requires a laboratory protocol or guide to achieve such objectives.…”
Section: Introductionmentioning
confidence: 99%